RF Performance of Layer-Structured Broadband Passive Millimeter-Wave Imaging System - Kunio Sakakibara; Kunihiko Ohkawa; Yutaka Aoki; Nobuyoshi Kikuma (International Journal of Antennas and Propagation)
Low profile and simple configuration are advantageous for RF module in passive millimeter-wave imaging system. High sensitivity over broad operation bandwidth is also necessary to detect right information from weak signal. We propose a broadband layer-structured module with low profile, simple structure, and ease of manufacture. This module is composed of a lens antenna and a detector module that consists of a detector circuit and a broadband microstrip-to-waveguide transition. The module forms a layer structure as a printed substrate with detector circuit is fixed between two metal plates with horn antennas and back-short waveguides. We developed a broadband passive millimeter-wave imaging module composed of a lens antenna and a detector module in this work. The gain and the antenna efficiency were measured, and the broadband operation was observed for the lens antenna. For the detector module, peak sensitivity was 8100 V/W. Furthermore, the detector module recognized a difference in the absorber’s temperature. The designs of the lens antenna and the detector module are presented and the RF performances of these components are reported. Finally, passive millimeter-wave imaging of a car, a human, and a metal plate in clothes is demonstrated in this paper.